Strategy modulates spatial perspective-taking: evidence for dissociable disembodied and embodied routes - Gardner, Mark; Brazier, Mark; Edmonds, Caroline J.; Gronholm, Petra (Frontiers in Human Neuroscience, 2013)
Previous research provides evidence for a dissociable embodied route to spatial perspective-taking that is under strategic control. The present experiment investigated further the influence of strategy on spatial perspective-taking by assessing whether participants may also elect to employ a separable ‘disembodied’ route loading on inhibitory control mechanisms. Participants (N=92) undertook both the ‘own body transformation’ (OBT) perspective-taking task, requiring speeded spatial judgements made from the perspective of an observed figure, and a control task measuring ability to inhibit spatially compatible responses in the absence of a figure. Perspective-taking performance was found to be related to performance on the response inhibition control task, in that participants who tended to take longer to adopt a new perspective also tended to show a greater elevation in response times when inhibiting spatially compatible responses. This relationship was restricted to those participants reporting that they adopted the perspective of another by reversing left and right whenever confronted with a front-view figure; it was absent in those participants who reported perspective-taking by mentally transforming their spatial orientation to align with that of the figure. Combined with previously published results, these findings complete a double dissociation between embodied and disembodied routes to spatial perspective-taking, implying that spatial perspective-taking is subject to modulation by strategy, and suggesting that embodied routes to perspective-taking may place minimal demands on domain general executive functions.